Childhood Medicaid Coverage and Later-Life Health Care Utilization - Wherry, Laura R.; Miller, Sarah; Kaestner, Robert; Meyer, Bruce D. (The Review of Economics and Statistics, 2018)
Exploiting a discontinuity in childhood Medicaid eligibility based on date of birth, we find that more years of childhood eligibility are associated with fewer hospitalizations in adulthood. For blacks, we find a 7% to 15% decrease in hospitalizations and a suggestive 2% to 5% decrease in emergency department visits, but no similar effect for nonblacks. The effects are pronounced for utilization related to chronic illnesses and for patients living in low-income postal codes. Calculations suggest that lower rates of hospitalizations during one year in adulthood for blacks offset between 2% and 4% of the initial costs of expanding Medicaid for all children.